BIOCHEMICAL STUDY OF THE EFFECTS OF LOW EXPOSURE IONIZING RADIATION DOSES ON THE OPERATORS OF ALTUWAITHA SITE - Shaymaa Saadi Abbood; Amel Jabbar Mutar (Scholar Express Journals, 2023)
Concerns have arisen about the effects of increased exposure to low ionizing radiation and how it impacts physiological processes. As a result, a study was conducted to investigate the impact of radiation exposure on workers at AL Tuwaitha nuclear research center site, specifically on their lipid profile, liver and kidney function. Workers at the nuclear test site are vulnerable to both internal and external radiation, making long-term exposure particularly concerning. In order to assess the effects of radiation, 100 adult subjects between the ages of 22-60 working at the site were subjected to biochemical test analysis, in addition to a control group of 50 adult subjects aged 24-60 residing outside the nuclear center. This study was conducted from September to December in 2022. At the Al-Tuwaitha site, the Directorate of Central Laboratories conducted the study. Using a disposable 5 mL syringe, human peripheral blood was collected from each participant via venipuncture. After withdrawing the blood, it was put into a centrifuge at 3000 rpm for ten minutes. The specimen was then placed in an Eppendorf tube. These samples were stored in a freezer at a constant -20 degrees Celsius. Then put it to use.
Keywords: Ionizing radiation; Liver function; Uric acid; Urea